Who’s Afraid of Virginia’s you: a Corpus-based Study of the French Translations of The Waves - Bosseaux, Charlotte (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2006)
AbstractThe present paper discusses issues related to the translation of the English personal pronoun you in the French translations of Virginia Woolf’s The Waves (1931). There are two published French translations of The Waves. The first one, Les Vagues, was translated by Marguerite Yourcenar and published in 1937. Around fifty years later, another version was published, under the same title but this time translated by Cécile Wajsbrot (1993). The two versions differ significantly when the use of tu and vous is concerned. This paper is concerned specifically with the original’s mind-style (Fowler 1977) in other words, the way the characters’ perceptions and thoughts, as well as their speech, are presented through language and how this is rendered in the translations. The quantitative analysis was realised using corpus-based studies tools which proved to be an asset in helping to identify the novels’ mind-style.